Correspondence between Florence O'Donoghue and various individuals regarding the publication of O'Donoghue's life of Liam Lynch in serial form in the 'Sunday Press' and in book form by the 'Irish Press' - O'Donoghue, Florence, 1895-1967; Feehan, Matthew, Colonel, 1913-1990 (1954)
Correspondents includes members of staff at the 'Sunday Press' and the 'Irish Press' including Matthew Feehan, Anna Kelly, Maurice Cronin and others. Correspondence relates to the publication and sales of O'Donoghue's book. Also includes mock ups of the proposed cover of the book. Also includes original red sleeve.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Lynch, Liam, -- 1893-1923; Irish Republican Army; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-